Montgomery's auditing (John Wiley & Sons, 1998)
Montgomery's Auditing is the definitive handbook on auditing, and this Continuing Professional Education version is a professional edition of the successful subscription reference, providing a condensed, yet complete overview of auditing for the professional as well as the senior level student. The strategies contained help to strengthen the auditor's skills in the profession's core service-audits conducted in accordance with GAAS of financial statements prepared in conformity with GAAP.